Design and Build Housekeeping System PT. Support Sentra Service - Siti Soleka; Sharyanto; Bernadus Gunawan Sudarsono (Yayasan Bina Internusa Mabarindo, 2022)
PT. Sentra Support Service is a company engaged in cleaning services and gardening services for office buildings, factories and malls. Of course, PT. The Support Service Center also provides trained workforce supported by quality equipment and equipment for positions such as administrative staff, production operators, security, tellers and other trained personnel according to the needs of service users. The problem that occurs in this case when the cleaner makes daily activity reports is still done manually, namely by writing activity reports that have been done in a notebook or paper. At this time, the workforce at PT. Sentra Support Service still uses logbooks or notebooks in writing daily activity reports. This is not very effective because the cleaners have to take turns writing their reports in one book and it is very impractical because the reports that are written have to wait in a queue, which takes time. For the method of analysis and design, they used Unified Modeling Language (UML). Housekeeping Information System at PT. The Web-Based Support Service Center uses the PHP and MySQL programming languages as its database. With this housekeeping information system, it can help companies with cleaning services.